Musculoskeletal symptoms in nursing students during clinical training: a pilot study - Pisco Alves Gomes, Jacinta Maria; Matos, Maria João; Fonseca, Maria José; Soares, Salete (Portuguese Rehabilitation Nursing Journal, 2025)
Introduction: Musculoskeletal symptoms are common among nursing students doing clinical teaching. The intervention of the Rehabilitation Nurse Specialist is fundamental in training students through an integrative program. This study aims to describe musculoskeletal symptoms in nursing students before and after clinical teaching and to analyze the implications and degree of satisfaction of ergonomics training. Methodology: As part of a research project into musculoskeletal symptoms, this research is a pilot study of a quantitative, exploratory and longitudinal nature. A non-probabilistic convenience sample, it included students from the Nursing Degree Course in clinical teaching in a hospital context. Instruments: Sociodemographic questionnaire; Satisfaction questionnaire and the Nordic Musculoskeletal Questionnaire. The latter questionnaire was administered before and after several clinical courses in a hospital setting, about a year apart. A training intervention on ergonomics was carried out between the first and second moments of data collection. Descriptive statistics were carried out using SPSS 28.0. Results: The sample consisted of 71 students from the Nursing Degree Course (3rd year) at the beginning and 33 at the end, mostly female and with no training/information in Ergonomics, aged between 20 and 25. Before starting the clinical sessions, it was found that in the last 12 months their complaints were mainly in the lumbar, cervical and thoracic regions, with a pain level between 2 and 4 on the numerical scale included in the Nordic Musculoskeletal Questionnaire. After several clinical sessions in a hospital setting, it was found that the most problematic area was the lumbar region and the pain level was between 2 and 5. Conclusion: After the training intervention, there was a reduction in the number of complaints in all areas.